Pengaruh Pemangkasan Cabang dan Pemberian Pupuk Pelengkap Cair dengan Frequensi Berbeda terhadap Pertumbuhan dan Hasil Tanaman Semangka Kuning (Citrullus lanatus) di Lahan Lebak - Iin Siti Aminah; Rosmiah Rosmiah; Erni Hawayanti; Dessy Tri Astuti; Maulana Tinto Anggoro (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Aminah IS, Rosmiah R, Hawayanti E, Astuti DT,. Anggoro MT. 2021. Effect of Branch Pruning and Application of Liquid Complementary Fertilizer with Different Frequency on Growth and Yield of Yellow Watermelon (Citrullus lanatus). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 595-602. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Watermelon is a plant that has high economic value, while in South Sumatra this plant has increased from 2016 to 2019. One of the efforts to increase the yield and quality of fruit is through cultivators. The research was carried out from June to September 2019 in farmers' gardens in the village of Tanjung Steko, North Indralaya Km 32, Ogan Ilir Regency, South Sumatra. This study used an experimental method with split plot design, namely pruning (P) as the main plot, P0 treatment without pruning, P1 with pruning, as subplots, namely the frequency of liquid fertilizer application (PPC) F1: 3 times, F2: 5times and F3 : 7times giving PPC. Plant variables included plant length, number of primary branches, age of flowering, weight of plant fruit, weight of fruit per plot. The results showed that branch pruning on watermelon plants showed the highest yields and on the variables of height, number of branches, and fruit weight, while the best application of liquid fertilizer was given with a frequency of 7 times. The highest weight yield was through branch pruning with a frequency of 7 times, that is 4.78 kg